2015
DOI: 10.1038/nature15510
|View full text |Cite|
|
Sign up to set email alerts
|

CMT2D neuropathy is linked to the neomorphic binding activity of glycyl-tRNA synthetase

Abstract: Summary Selective neuronal loss is a hallmark of neurodegenerative diseases, which counter-intuitively are often caused by mutations in widely-expressed genes1. Charcot-Marie-Tooth (CMT) diseases are the most common hereditary peripheral neuropathies, for which there are no effective therapies2,3. A subtype of the diseases—CMT2D—is caused by dominant mutations in GARS, encoding the ubiquitously expressed enzyme glycyl-tRNA synthetase (GlyRS). Despite the broad requirement of GlyRS for protein biosynthesis in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
200
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(216 citation statements)
references
References 41 publications
12
200
0
2
Order By: Relevance
“…Although we do not directly show that sensory identity is perturbed during embryonic development, we do observe defective sensory nerve branching in the mutant hind paw at E13.5 ( Fig. 5F), similar to the previously reported embryonic impairment in facial motor neuron migration (18) and suggestive of developmental onset. However, the subtype identity defect appears to be sensory specific, as mutant Gars mice do not show a difference in the proportion of α-and γ-motor neurons (SI Appendix, Fig.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Although we do not directly show that sensory identity is perturbed during embryonic development, we do observe defective sensory nerve branching in the mutant hind paw at E13.5 ( Fig. 5F), similar to the previously reported embryonic impairment in facial motor neuron migration (18) and suggestive of developmental onset. However, the subtype identity defect appears to be sensory specific, as mutant Gars mice do not show a difference in the proportion of α-and γ-motor neurons (SI Appendix, Fig.…”
Section: Discussionsupporting
confidence: 70%
“…CMT2D-associated mutant GlyRS was recently shown to aberrantly bind to the neuronal receptor protein NRP1 and antagonize its activity (18). Although NRP1 was the focus of that study, mutant GlyRS was shown to interact with a number of other proteins found on the neuronal surface, albeit to a lesser degree (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Collectively, these results suggested that regulation occurred due to negative feedback among TyrRS, PARP1, and SIRT1 under oxidative stress. In addition to their aminoacylation functions in protein synthesis, many aminoacyl-tRNA synthetases, including TyrRS, have been shown to take on multiple roles (41)(42)(43). Specifically, TyrRS was found to act as a sensor for oxidative stress after translocating to the nucleus, where it activates DNA damage repair genes that are downstream of E2F1 (7).…”
Section: Discussionmentioning
confidence: 99%